Understanding Descriptive Statistics: A college based approach in Zimbabwe - Rupi, Edwin (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The main focus of this paper was to describe how much, data values, spread out from oneanother and how they relate to each other. Calculations of variance and standard deviationhelped describe the nature of scores recorded for classroom situations. Just like the stem andleaf plot we saw from the box and whisker plot that the data are either negatively orpositively skewed depending on the length of whiskers to the left or right. The box andwhisker plot was used to identify some outliers, that is, values more extreme than thewhiskers. The box plot is thus useful in spotting data dispersion, screening data or singlingout potential problem data before any analysis. The scatter diagram proved more important intrying to describe relationships between two variables measured on the same subject. Thisarticle also looked at the two major types of correlation coefficients (Pearson and Spearman)and their calculations. The meaning of each value was also scrutinised stemming from itssize.